Analisis Desain Bukaan Ventilasi Terhadap Arah Aliran Angin pada Rumah Tinggal - Misman, Archie Gilliant; Sangkertadi, Sangkertadi; Wuisang, Cynthia E. V. (Universitas Bina Taruna Gorontalo, 2025)
This research aims to analyze the effect of the design of ventilation in residential houses at the Royal Residence on the direction of incoming wind flow to increase indoor thermal comfort. The research was carried out using quantitative methods, where values ​​were taken by direct measurements at the location and then analyzed using CFD simulations Cradle CFD and Energy 2D. The research results show that the existing ventilation design of Casement Top Hung produces an average indoor wind speed of 0.281 m/s, not good enough to flow air into the room evenly, the Vertically Pivoted type produces an average wind speed of 1.28 m/s, and the air is channeled evenly so that the wind that enters the room provides thermal comfort to the occupants. The direction of the opening greatly influences the speed and distribution of incoming air to support air comfortable for people. The landscape greatly affects the placement of openings and the types of windows where wind can be spread throughout the room evenly to provide thermal comfort for occupants. These results can be used as an evaluation in trends of selection window types and for further research in improving the thermal comfort of residential in different landscape environmental conditions.